Outcome of Oral Steroids After Optical Internal Urethrotomy (OIU) In Comparison eith OIU Only - Perveg, Md Akter Kamal; Rahman, Md Habibur; Alam, AKM Khurshidul; Ghosh, Kartik Chandra; Hossain, Md Shamim; Rabbani, Rezwanul Haque (Bangladesh Journal of Urology, 2023)
Objectives: To evaluate the effects of Oral Steroid as Tablet Deflazacort(6mg) in the prevention of recurrence of short segment anterior urethral stricture after optical internal urethrotomy compare with OIU only. Material and methods: This present Randomized clinical comparative study was designed to observe the efficacy of Oral Steroid as Tablet Deflazacort (6mg) after optical internal urethrotomy. All male patients of age between 18-45 years, who were diagnosed as short segment anterior urethral stricture(<1.5cm) and planned for optical internal urethrotomy, were divided into two groups after fulfilling selection criteria. After informed consent and random allocation by lottery, patients under group A were given oral steroid as Tab. Deflazacort (6mg) twice daily for 2weeks then once daily for another 2weeks after catheter removal on 7th post-operative day following optical internal urethrotomy, while patients under group B were managed by optical internal urethrotomy only. 26 patients were enrolled in group A and 25 patients in group B. In group A, 4 patients and group B, 3 patients were lost during follow up. Hence total of 44 patients completed the study with 22 patients in each group, during the period of January 2018 to December 2018. Result: In present study, there were no significant differences found in age, preoperative American urological association (AUA) score, preoperative maximum urinary flow rate, and preoperative PVR between two groups. Postoperative comparison of AUA score at 6th month follow up between two groups showed the decrease in AUA score in group A in compare to group B and the difference was statistically significant (5.8±5.1 versus 10.9±7.1, p=0.009). Maximum flow rates at 3rd month (23.7±5.8 ml/sec versus 20.0±2.9 ml/sec( p= 0.010) and 6th month (20.0±5.2 ml/sec versus 15.9±5.8 ml/sec, p=0.018) follow up were significantly higher in group A than group B. Post void residual urine were significantly decrease in group A than group B (21.5±26.5 ml versus 42.0±30.9 ml, P=0.023). Study also showed a significant reduction in recurrence of anterior urethral stricture of 3(13.6 %) in the group A versus 9 (40.9% ) in the group B (p=0.042). Conclusion: Use of the Oral steroid after optical internal urethrotomy in preventing recurrence of short segment anterior urethral strictures were effective. Bangladesh J. Urol. 2023; 26(1): 22-27